Portuguese football coaches' migration: Patterns and networks in 2009-2013 - Mario Borges; Antonio Rosado; Rita de Oliveira; Francisco Freitas (Universidad Pablo de Olavide, 2020)
Sport migration is an important topic of global  migration. It can capture migration patterns and the reliance on networks, which are specific to sports. This study seeks to identify the patterns and networks of Portuguese football coaches' migration between 2009 and 2013. This period is important because these were years of financial crisis with high rates of unemployment. We collected data about destination countries of migrant coaches. For coaches working abroad in 2013, we also collected data about their career path and networks including the assistant coaches and players with whom they had previously worked. The results showed that the destination of Portuguese football coaches involves both peripheral and central areas of football prestige. The pattern of migration suggests an overlap of economic, historical and cultural factors. On the other hand, the network relations of Portuguese football coaches were prominent in a zone of high prestige close to the native country, and in a zone with high financial incentives but lower football prestige. Taken together, these results highlight the career specificities of coaches who migrate to different countries including the role of networks on a football coaching career abroad.